Method for producing tantalum powder by reducing tantalum oxide with alkaline earth metal
By using alkaline earth metal magnesium to reduce tantalum oxide powder in a hydrogen-containing atmosphere, the method of preparing tantalum powder is solved, and the problems of complex processes, large energy consumption and safety hazards in the prior art are achieved, and the high electrical performance and process simplification and safety improvement of tantalum powder are achieved.
Patent Information
- Application Number
- CN202480002565.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-04-01
AI Technical Summary
The prior art when preparing capacitor-grade tantalum powder, the process is complex, the energy consumption is high, and the use of a large number of alkaline earth metals poses a risk of fire safety, and the electrical performance is not ideal.
The method of preparing tantalum powder by reducing tantalum oxide powder such as magnesium in a hydrogen-containing atmosphere is adopted. The ratio of the Fischer particle size to the loose density of tantalum oxide powder is greater than 1.5. By simplifying the process and controlling the reaction conditions, the amount of alkaline earth metal is used and the risk of ignition is reduced.
The process is simplified and safety is improved, and the tantalum powder obtained has good electrical performance and is suitable for the manufacturing of high-voltage and high-reliability capacitors.
Smart Images

Figure CN119744208A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of smelting rare metal functional materials, and in particular relates to tantalum powder for making high-voltage and high-reliability capacitors and a manufacturing method thereof. Background Art
[0002] Tantalum electrolytic capacitors (hereinafter referred to as tantalum capacitors) have the advantages of high capacity, small size, strong self-healing ability, and high reliability. They are widely used in high-end technical fields such as communications, computers, automotive electronics, medical equipment, radar, aerospace, and automatic control devices. Tantalum powder is the key material for making tantalum capacitors. Only by using tantalum powder for capacitors with higher voltage resistance can tantalum capacitors with better reliability be produced. Therefore, only by continuously developing tantalum powder for capacitors with higher voltage resistance can the tantalum capacitors produced continue to meet the requirements of high-reliability development of electronic devices and electronic circuits.
[0003] At present, the main methods for industrial preparation of capacitor-grade tantalum powder are sodium reduction potassium fluorotantalate method, tantalum ingot hydrogenation method, magnesium reduction tantalum oxide method, etc. The sodium reduction potassium fluorotantalate method can easily prepare high specific capacity tantalum powder, but the problem is that the tantalum powder has low specific capacity, large leakage current, and low breakdown voltage under relatively high voltage energizing conditions. The tantalum powder prepared by the tantalum ingot hydrogenation method has excellent pressure resistance, but the problem is that the specific capacity of tantalum powder is generally low. In order to continuously improve the pressure resistance of tantalum powder and at the same time increase the specific capacity of tantalum powder, the magnesium reduction tantalum oxide method has been successfully developed and continuously developed. The magnesium reduction tantalum oxide method changes the state of the reactants and is expected to produce tantalum powder for capacitors with improved specific capacity and pressure resistance.
[0004] CN114192791B discloses a method for producing tantalum powder for capacitors by reducing tantalum oxide with alkaline earth metal. The method is to add alkali metal or alkaline earth metal halide during the reduction process, use excess alkaline earth metal to reduce at a high temperature above 700°C in a heating furnace filled with inert gas, separate the excess alkaline earth metal from the tantalum-containing material after the reduction, and then further sinter the material at a high temperature above 750°C, but the method is not perfect. The possible problem is that if the temperature and time, the amount of halide and magnesium added, and the amount of additives used are adjusted as described in the patent, the specific capacity of tantalum powder will be limited, and the adjustment range is too large, even resulting in a certain degree of deterioration of key properties such as breakdown voltage and leakage current. Therefore, the method for preparing tantalum powder cannot meet the market's diversified demand for tantalum powders with different specific capacities. Moreover, the process is relatively complicated, requires a separate sintering step, and consumes a lot of energy. The safety of the process also has room for improvement.
[0005] There is also a method of preparing tantalum powder by self-propagating high temperature synthesis (SHS) in the prior art. However, this method needs to be carried out at a temperature of at least 2000°C, and the reaction is too fast, which is not only difficult to control, but also has too high requirements on process equipment. In addition, the obtained tantalum powder is also uneven and cannot meet the needs of manufacturing high-reliability capacitors.
[0006] Without being bound by general theories, the inventors have found through extensive research that the existing processes for preparing tantalum powder are relatively complex, consume a lot of energy, and / or, due to the use of a large amount of alkaline earth metal, there is a safety hazard of ignition of the alkaline earth metal during reduction. Moreover, the electrical properties (especially residual current and / or breakdown voltage, etc.) are not ideal. Summary of the invention
[0007] An object of the present invention is to provide a method for preparing tantalum powder by reducing tantalum oxide powder with an alkaline earth metal such as magnesium in a hydrogen-containing atmosphere, wherein the tantalum oxide powder has a similar particle size (in μm) to the bulk density (in g / cm 3 The ratio of the particle size is greater than 1.5 (for example, the particle size of the Feldspar is 6.78 μm, and the bulk density is 2.3 g / cm 3 , then the ratio of the two is 6.78÷2.3=2.95), and the purity is preferably above 99.95%. The method for producing tantalum powder can reduce the amount of alkaline earth metal added, and the safety risk of alkaline earth metal ignition when it is taken out of the furnace after the reduction is completed is greatly reduced.
[0008] The tantalum oxide powder used as a raw material in the present invention is characterized in that the ratio of the Fisher particle size to the bulk density is greater than 1.5, preferably greater than 2.0, more preferably greater than 2.5, more preferably greater than 3.0, more preferably greater than 3.5, and more preferably greater than 4.5. In a preferred embodiment, the ratio is 2.0-15.0, more preferably 3.0-5.0. Preferably, the tantalum oxide powder has a purity of 99.95% or more, more preferably 99.995% or more. Generally speaking, the higher the purity of tantalum oxide, the more conducive it is to improving the electrical properties of tantalum powder.
[0009] Tantalum oxide is generally a popular name for tantalum pentoxide. In this article, they can be used interchangeably to represent Ta 2 O 5 .
[0010] The method of the present invention is simple in process, easier to operate and control, and safer in process. Moreover, the comprehensive electrical properties of the obtained tantalum powder are good.
[0011] Specifically, the present invention provides a method for preparing tantalum powder by reducing tantalum oxide with an alkaline earth metal such as magnesium, comprising the following steps:
[0012] (1) selecting tantalum oxide powder having a ratio of Fischer-Tropsch particle size to bulk density greater than 1.5 as a raw material, mixing the tantalum oxide powder with an excess of an alkaline earth metal reducing agent, and simultaneously mixing in 10-200% by weight of at least one alkali metal and / or alkaline earth metal halide, placing the mixture in a sealed reaction container, extracting air from the container, and placing the container in a heating furnace;
[0013] (2) raising the temperature of the heating furnace to 700-1000° C. and maintaining the temperature for, for example, 1-3 hours to allow the tantalum oxide to fully react with the reducing agent;
[0014] (3) After the insulation is completed, the temperature of the heating furnace is set at 600-750° C. (preferably 620-680° C., such as 640° C.), the heating furnace is evacuated, for example, to below 10 Pa, and the temperature is maintained under negative pressure (for example, for 1-10 hours);
[0015] (4) Then, an inert gas is filled into the reaction container to maintain a positive pressure in the reaction container, and then the reaction container is cooled to room temperature and passivated to obtain a mixture containing a halide and tantalum powder;
[0016] (5) separating tantalum powder from the obtained mixture, for example, by washing with water, washing with acid, filtering, or drying.
[0017] Wherein, in step (1), after the air in the container is evacuated, the reaction container is provided with a hydrogen-containing gas, which is achieved, for example, by introducing a hydrogen-containing gas, or by adding a liquid or solid hydrogen-containing substance (preferably a solid hydrogen-containing substance) and causing it to release hydrogen. Preferably, in the latter case, the hydrogen-containing substance is separated from other raw materials such as tantalum oxide powder, alkali metal and / or alkaline earth metal halide, which can be achieved, for example, by placing the hydrogen-containing substance alone in a crucible. Preferably, the hydrogen-containing substance is, for example, a substance that can release hydrogen at high temperature, such as tantalum powder adsorbed with hydrogen (also referred to as hydrogen-containing tantalum powder), hydrogen-containing niobium powder, hydrogen-containing titanium powder, and hydrogen-containing compounds. Preferably, hydrogen-containing tantalum powder is used.
[0018] Preferably, the ratio of the tantalum oxide used as the raw material in step (1) is greater than 2.0, preferably greater than 3.0, more preferably greater than 3.5, and more preferably greater than 4.5. In a preferred embodiment, the ratio is 2.0-15.0, more preferably 3.0-5.0. Preferably, the purity is greater than 99.95%, more preferably greater than 99.995%. Generally speaking, the higher the purity of tantalum oxide, the more conducive it is to improving the electrical properties of tantalum powder.
[0019] The alkaline earth metal reducing agent described in step (1) is preferably magnesium, more preferably magnesium particles, more preferably magnesium particles with a purity of 3N5 (i.e., 99.95%) or more, and the higher the purity of the magnesium particles, the better. There is no restriction on the particle size of the magnesium particles. However, after a lot of research, the inventors found that magnesium particles with a particle size of 150-4000 μm are more suitable for this technology, and the tantalum powder obtained by reduction has better pressure resistance. Magnesium particles in this particle size range are not only conducive to the safety of the storage and transportation process of metal magnesium, but also conducive to uniform mixing. If the magnesium particles are too fine, the activity is too strong and it is easy to spontaneously ignite; if the magnesium particles are too coarse, it is not conducive to uniform mixing and is not conducive to the optimization of tantalum powder performance. The amount of excess reducing agent added refers to the amount exceeding the theoretical amount for completely reducing tantalum oxide. In the present invention, it is preferably 5-50% of the theoretical amount, preferably 10-48%, more preferably 10-45%, and more preferably 10-15% or 5-10%, or 15-20%. Generally speaking, the theoretical amount of magnesium required to completely reduce one kilogram of tantalum oxide is about 0.273 kilograms.
[0020] In step (2), due to the heat of reduction, the tantalum powder inevitably undergoes a certain degree of sintering. The presence of hydrogen-containing gas in the container further enhances the sintering of the tantalum powder, thereby omitting a separate subsequent sintering step. Since a separate sintering step is often required in the prior art, this undoubtedly simplifies the process relative to the prior art. Moreover, the sintering and reduction under the conditions of the present invention are carried out simultaneously and cooperate with each other, making it easier to obtain tantalum powder with improved microstructure, which is unexpected.
[0021] The added weight of the alkali metal and / or alkaline earth metal halide in step (1) is preferably 10-180% of the weight of tantalum oxide, preferably 25-120%, more preferably 70-120% or 100-180%, most preferably 15-80%, for example 25-80%. The alkali metal or alkaline earth halide is preferably analytically pure, preferably of higher purity. The alkali metal or alkaline earth halide is preferably in the form of particles. There is no limitation on its particle size, but the inventors have found that particles of 70 μm-4000 μm are more suitable for the present technology, and the tantalum powder obtained by reduction has better pressure resistance.
[0022] Preferably, the alkali metal or alkaline earth metal halide in step (1) is NaCl, KCl, KF, KI, and / or MgCl 2 The alkali metal halide may be sodium chloride and / or potassium chloride. Preferably, it is a mixture of sodium chloride and potassium chloride, more preferably, the ratio of sodium chloride to potassium chloride in the mixture is 1:1-10, most preferably about 1:1.
[0023] Preferably, in step (1), one or more compounds containing B, P, and / or N elements may be added as additives to dope the tantalum powder. In terms of the amount of effective elements, the amount of B element added is preferably 1-100 ppm, more preferably 20-60 ppm; the amount of P element added is preferably 10-200 ppm, more preferably 30-90 ppm; the amount of N element added is preferably 300-2500 ppm, more preferably 500-1200 ppm. It should be understood that although compounds are added here, the effective elements are B, P, and / or N, so the amounts mentioned here are calculated based on the amounts of B, P, and / or N.
[0024] Preferably, in step (2), the heating furnace is heated to 750-1000° C. More preferably, the heating furnace is heated to 900-965° C.
[0025] The hydrogen-containing gas used in step (1) is pure hydrogen or a mixture of hydrogen and an inert gas. The hydrogen may be gaseous hydrogen or other liquid or solid hydrogen-containing substances that are heated to release hydrogen. Although hydrogen is a common reducing agent, it cannot reduce tantalum oxide. In other words, hydrogen cannot act as a reducing agent in the present invention. However, the inventors unexpectedly discovered that since hydrogen strengthens the sintering that accompanies the reduction process, the process can be significantly simplified by omitting the sintering step. Moreover, the introduction of hydrogen as a medium may reduce the amount of alkaline earth metal added as a reducing agent, and may also improve the electrical properties of the product, especially the residual current and / or breakdown voltage.
[0026] Preferably, in step (1), the gas pressure of the reaction container is positive. The hydrogen partial pressure in the container exceeds 0.050KPa, preferably 0.1-200KPa, more preferably 0.3-50KPa, more preferably 10-20KPa, more preferably 0.5-10KPa or 10-15KPa, more preferably 0.1-0.3KPa. Too low hydrogen partial pressure cannot promote the reduction effect well, so the hydrogen partial pressure should not be too low; conversely, after the hydrogen partial pressure is increased to a certain extent, the ability to further improve is weakened, and from the perspective of ensuring the absolute safety of hydrogen use, it is preferred to avoid too high hydrogen partial pressure.
[0027] Inert gas generally refers to rare gases, such as helium, neon, and argon. Although nitrogen is sometimes regarded as an inert gas due to its stable properties, in the art, due to its relatively high reduction temperature, nitrogen is very active at this high temperature and is generally considered unsuitable as an inert protective gas. However, after extensive research, the inventors found that a small amount of nitrogen in the above-mentioned inert gas does not damage the overall inert protective atmosphere, and can also achieve nitrogen doping of tantalum powder. From the perspective of achieving a better nitrogen doping effect of tantalum powder, in step (1), when a mixture of hydrogen-containing gas and inert gas is used, the mixture may preferably contain 0.5-10% nitrogen, calculated based on the total amount of hydrogen and inert gas.
[0028] In step (3), since the melting point of metallic magnesium is relatively high, it is difficult for magnesium vapor to diffuse to the outside of the reactor, but it condenses into a solid in the low temperature area of the reactor, thereby achieving separation.
[0029] Preferably, in step (3), the temperature of the heating furnace is 600-750° C. More preferably, the temperature of the heating furnace is raised to 620-680° C. Preferably, the heating furnace is evacuated to below 5 Pa, preferably below 0.5 Pa.
[0030] If a mixture of an inert gas and hydrogen is introduced as the hydrogen-containing atmosphere in step (1), the inert atmosphere may be the same as or different from the inert gas in step (4). Preferably, in step (1) and / or (4), a positive pressure is maintained in the reactor. Preferably, in step (3), a positive pressure in the reactor is avoided because a positive pressure is not conducive to the separation of excess alkaline earth metals such as magnesium.
[0031] Preferably, the method of the present invention further comprises heat treatment such as high temperature and high vacuum heat treatment (or high temperature and high vacuum heat treatment after sintering according to patent CN114210973B), oxygen reduction, acid washing after step (5), and then tantalum powder is separated by filtering and drying, so that tantalum powder suitable for making high-reliability tantalum capacitors can be obtained. These treatments are all known processes in the prior art. In other words, these treatments can adopt any process known in the prior art. For example, the high-temperature and high-vacuum heat treatment and passivation here can adopt the methods provided by patents CN201110039272.9, CN201120077798.1, CN201120077680.9, CN201120077305.4, etc., the oxygen reduction can adopt the method provided by patent CN201420777210.7, and the pickling can adopt the methods provided by patents CN201210548101.3, CN201280077499.5, CN201210548008.2, etc.
[0032] As an alternative to doping N, P and / or B elements in step (1), the present invention may also include a separate step of doping these elements, for example, after step (5). Of course, raw materials containing these elements may also be used directly. These elements may also be added in the aforementioned high temperature and high vacuum heat treatment step. It is particularly preferred to add the P element. Adding the P element can increase the specific volume. As long as the total amount of P doping is controlled, the effect of increasing the specific volume is the same regardless of when it is added.
[0033] The tantalum powder of the above product is pressed into blocks, sintered, and energized under high voltage conditions. The electrical properties of the energized blocks are tested, and it is found that the energized blocks have good electrical properties, especially residual current. Therefore, the tantalum powder manufactured by the present invention is more suitable for making high-voltage and high-reliability tantalum capacitors.
[0034] Moreover, the process of the present invention is simple and easy to control. For example, in all steps of the present invention, microwaves are not used, and excessively high temperatures are not used, and the proportion of alkaline earth metal used for reduction is lower. Therefore, the equipment used is also relatively simple, and the tantalum powder preparation process is safer.
[0035] Without being bound by general theories, combined with the theoretical analysis principle of powder liquid phase sintering, the inventor believes that the reason why the present invention achieves excellent results is as follows: in step (2), when there is a hydrogen-containing gas in the atmosphere of the reactor, the hydrogen-containing gas makes reduction easier to occur and can also strengthen sintering, so that it is easier to build a spatial structure suitable for capacitor production between tantalum powder particles, and the tantalum powder particles are more uniform in size, smooth in particles, thick in sintering necks, and less in ultrafine particles. Thereafter, the obtained tantalum powder is subjected to high-temperature and high-vacuum heat treatment according to the prior art (or first subjected to high-temperature and high-vacuum heat treatment according to patent CN114210973B after sintering), deoxidation, and pickling treatment, and tantalum powder suitable for preparing high-voltage and high-reliability capacitors is obtained.
[0036] The “easier to construct a space structure suitable for capacitors” mentioned here means that after the obtained tantalum powder is pressed and sintered to make an anode block, there are no ultrafine pores in the obtained anode block. These ultrafine pores are not good for electrical properties, especially leakage current and ESR (equivalent series resistance).
[0037] The present invention also relates to tantalum powder prepared by the above method, an anode block made of the tantalum powder, and use of the tantalum powder and / or the anode block in making capacitors. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] The following drawings are provided for a better understanding of the present invention. These drawings are exemplary and are not intended to limit the scope of the present invention.
[0039] Figure 1 The scanning electron microscope picture of the tantalum powder obtained according to the present invention is given.
[0040] The accompanying figure illustrates that the obtained tantalum powder has a more uniform particle size, smooth particles, a thick sintering neck, and fewer ultrafine particles. DETAILED DESCRIPTION
[0041] In order to further illustrate the present invention, the preferred embodiments of the present invention are described below in conjunction with the examples, and it can be clearly seen that the objects, features and advantages of the present invention. However, these descriptions are only for further illustrating the features and advantages of the present invention, rather than for limiting the present invention. If the specific conditions are not specified in the examples, they are carried out under normal conditions. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0042] For the purpose of this specification, all numbers indicating the amount of ingredients, reaction conditions, etc. in the specification and claims should be understood as being modified by the term "about" in all cases, unless otherwise specified. Accordingly, the numerical parameters given in the following specification and the appended claims are approximate values, which may vary according to the desired properties that the present invention attempts to obtain, unless otherwise indicated. At least, and without intending to limit the application of the doctrine of equivalents to the scope of the claims, each numerical parameter should be interpreted at least in accordance with the number of reported significant figures and in accordance with conventional rounding techniques.
[0043] The analysis of impurity content in tantalum powder is carried out in accordance with the Chinese standard GB / T15076.1~15076.15, and the physical properties are carried out in accordance with the provisions of the industry standard YS / T573-2015. The test of electrical properties in tantalum powder is carried out in accordance with the provisions of the Chinese standard GB / T3137.
[0044] Example 1
[0045] Take 40.0kg of tantalum oxide, the particle size of which is 10.92μm and the bulk density is 2.6g / cm 3, the numerical ratio is 10.92÷2.6=4.2, and the purity is 99.997%. Add 15.5kg of magnesium particles, and add 5.0kg of potassium chloride (KCl) and 5.0kg of sodium chloride (NaCl) at the same time, mix well and put into a closed reaction container, separate (i.e. extract) the air in the reaction container. Pass a mixture of hydrogen and argon into the reaction container, control the hydrogen partial pressure to 50KPa, and keep the reaction container under positive pressure. Put the reaction container in a heating furnace and heat it to 950℃, keep it warm for 2.0 hours, so that the tantalum oxide is fully reduced. Then, reduce the temperature to 640℃ to evacuate, reduce the pressure in the reaction container to 5.7Pa, keep it warm for 18 hours, and stop evacuating. Then, argon gas is introduced into the reaction container and the temperature is lowered to room temperature for passivation treatment. After the passivation is completed, the magnesium metal is taken out of the furnace. When taken out of the furnace, the metal magnesium is stable and there is no ignition and smoke. Then, the obtained mixture of halide and tantalum powder is washed with water, acid washed, filtered, and dried to separate the tantalum powder. The values of the tantalum oxide Fetter particle size, bulk density, purity, reduction temperature, etc. are listed in Table 1.
[0046] Then, the tantalum powder was heated at 1450°C and below 5.0×10 -3 Pa pressure, high temperature and high vacuum heat treatment for 1.0 hour, and then deoxidation and pickling are carried out to obtain the final tantalum powder. According to the anode block mass, pressing density, anode block sintering temperature, sintering time specified in Table 1, and other conditions according to the aforementioned GB / T3137 requirements, the final tantalum powder obtained is made into anode blocks, energized under 300V conditions, and then the electrical properties are tested according to the aforementioned GB / T3137 requirements. In the specific capacitance test, 30% H 2 SO 4 After the solution test, 10% H 3 PO 4 Solution test, the measured results are listed in Table 2.
[0047] Comparative Example 1
[0048] Take 40.0kg of tantalum oxide, the particle size of which is 3.41μm and the bulk density is 2.5g / cm 3, the numerical ratio is 3.41÷2.5=1.36, and the purity is 99.997%. Add 15.5kg of magnesium particles, and add 5.0kg of potassium chloride (KCl) and 5.0kg of sodium chloride (NaCl) at the same time, mix well and put into a closed reaction container, separate (i.e., extract) the air in the reaction container. Pass argon gas into the reaction container, and put the reaction container into a heating furnace to heat it while maintaining positive pressure in the reaction container, raise the temperature to 950℃, and keep it warm for 2.0 hours to fully reduce the tantalum oxide. Then, reduce the temperature to 640℃ to evacuate, reduce the pressure in the reaction container to 5.7Pa, keep it warm for 18 hours, and stop evacuating. Then, argon gas is introduced into the reaction container and the temperature is lowered to room temperature for passivation treatment. After the passivation is completed, the magnesium metal is taken out of the furnace. When taken out of the furnace, the metal magnesium is stable and there is no ignition and smoke. Then, the obtained mixture of halide and tantalum powder is washed with water, acid washed, filtered, and dried to separate the tantalum powder. The values of the tantalum oxide Fetter particle size, bulk density, purity, reduction temperature, etc. are listed in Table 1.
[0049] Then, the tantalum powder was heated at 1450°C and below 5.0×10 -3 Pa pressure, high temperature and high vacuum heat treatment for 1.0 hour, and then deoxidation and pickling are carried out to obtain the final tantalum powder. According to the anode block mass, pressing density, anode block sintering temperature, sintering time specified in Table 1, and other conditions according to the aforementioned GB / T3137 requirements, the final tantalum powder obtained is made into anode blocks, energized under 300V conditions, and then the electrical properties are tested according to the aforementioned GB / T3137 requirements. In the specific capacitance test, 30% H 2 SO 4 After the solution test, 10% H 3 PO 4 Solution test, the measured results are listed in Table 2.
[0050] Example 2
[0051] Take 40.0kg of tantalum oxide, the particle size of which is 10.92μm and the bulk density is 2.6g / cm 3, the numerical ratio is 10.92÷2.6=4.2, and the purity is 99.997%. Add 15.5kg of magnesium particles, and add 5.0kg of potassium chloride (KCl) and 5.0kg of sodium chloride (NaCl) at the same time, mix well and put into a closed reaction container, separate (i.e. extract) the air in the reaction container. Pass a mixture of hydrogen and argon into the reaction container, control the hydrogen partial pressure to 50KPa, and keep the reaction container under positive pressure. Put the reaction container in a heating furnace and heat it to 950℃, keep it warm for 2.0 hours, so that the tantalum oxide is fully reduced. Then, reduce the temperature to 640℃ to evacuate, reduce the pressure in the reaction container to 5.7Pa, keep it warm for 18 hours, and stop evacuating. Then, argon gas is introduced into the reaction container and the temperature is lowered to room temperature for passivation treatment. After the passivation is completed, the magnesium metal is taken out of the furnace. When taken out of the furnace, the metal magnesium is stable and there is no ignition and smoke. Then, the obtained mixture of halide and tantalum powder is washed with water, acid washed, filtered, and dried to separate the tantalum powder. The values of the tantalum oxide Fetter particle size, bulk density, purity, reduction temperature, etc. are listed in Table 1.
[0052] Then, the tantalum powder was heated at 1450°C and below 5.0×10 -3 Pa pressure, high temperature and high vacuum heat treatment for 1.0 hour, and then deoxidation and pickling are carried out to obtain the final tantalum powder. According to the anode block mass, pressing density, anode block sintering temperature, sintering time specified in Table 1, and other conditions according to the aforementioned GB / T3137 requirements, the final tantalum powder obtained is made into anode blocks, energized under 300V conditions, and then the electrical properties are tested according to the aforementioned GB / T3137 requirements. In the specific capacitance test, 30% H 2 SO 4 After the solution test, 10% H 3 PO 4 Solution test, the measured results are listed in Table 2.
[0053] Comparative Example 2
[0054] Take 40.0kg of tantalum oxide, the particle size of which is 10.92μm and the bulk density is 2.6g / cm 3, the numerical ratio is 10.92÷2.6=4.2, and the purity is 99.997%. Add 15.5kg of magnesium particles, and add 5.0kg of potassium chloride (KCl) and 5.0kg of sodium chloride (NaCl) at the same time, mix well and put into a closed reaction container, separate (i.e., extract) the air in the reaction container. Pass argon gas into the reaction container, and put the reaction container into a heating furnace to heat it while maintaining positive pressure in the reaction container, raise the temperature to 950℃, and keep it warm for 2.0 hours to fully reduce the tantalum oxide. Then, reduce the temperature to 640℃ to evacuate, reduce the pressure in the reaction container to 5.7Pa, keep it warm for 18 hours, and stop evacuating. Then, argon gas is introduced into the reaction container and the temperature is lowered to room temperature for passivation treatment. After the passivation is completed, the magnesium metal is taken out of the furnace. When taken out of the furnace, the metal magnesium is stable and there is no ignition and smoke. Then, the obtained mixture of halide and tantalum powder is washed with water, acid washed, filtered, and dried to separate the tantalum powder. The values of the tantalum oxide Fetter particle size, bulk density, purity, reduction temperature, etc. are listed in Table 1.
[0055] Then, the tantalum powder was heated at 1450°C and below 5.0×10 -3 Pa pressure, high temperature and high vacuum heat treatment for 1.0 hour, and then deoxidation and pickling are carried out to obtain the final tantalum powder. According to the anode block mass, pressing density, anode block sintering temperature, sintering time specified in Table 1, and other conditions according to the aforementioned GB / T3137 requirements, the final tantalum powder obtained is made into anode blocks, energized under 300V conditions, and then the electrical properties are tested according to the aforementioned GB / T3137 requirements. In the specific capacitance test, 30% H 2 SO 4 After the solution test, 10% H 3 PO 4 Solution test, the measured results are listed in Table 2.
[0056] Example 3
[0057] Take 40.0kg of tantalum oxide, the particle size of which is 9.72μm and the bulk density is 2.1g / cm 3, the ratio of its test value is 9.72÷2.1=4.63, and the purity is 99.999%. Add 15.5kg of magnesium metal particles, and add 6.5kg of potassium chloride (KCl) and 6.5kg of sodium chloride (NaCl) at the same time, mix well and put into the reaction container, and separate the air in the reaction container. Pass a mixed gas of hydrogen and argon into the reaction container, control the hydrogen partial pressure to 30KPa, and keep the reaction container under positive pressure. Put the reaction container into a heating furnace and heat it to 940℃, keep it warm for 2.0 hours, then reduce the temperature to 650℃ to evacuate, reduce the pressure in the reaction container to 5.7Pa, keep it warm for 18 hours, and stop evacuating. Then, pass argon into the reaction container and cool it down to room temperature, and passivate it. After the passivation is completed, take it out of the furnace. When it is taken out of the furnace, the magnesium metal is stable and a small amount of smoke comes out; the obtained halide and tantalum powder mixture is washed, pickled, filtered, and dried to separate the tantalum powder. The values of tantalum oxide Fee particle size, bulk density, purity, reduction temperature, etc. are listed in Table 1.
[0058] Then, 50 ppm of P was added to the tantalum powder and heated to 1400°C and below 5.0×10 -3 Pa pressure, high temperature and high vacuum heat treatment for 1.0 hour, and then deoxidation and acid washing to obtain the final tantalum powder. According to the anode block mass, pressing density, anode block sintering temperature, sintering time specified in Table 1, and other conditions according to the aforementioned GB / T3137 requirements, the final tantalum powder obtained is made into an anode block, energized under 200V conditions, and then the electrical properties are tested according to the aforementioned GB / T3137 requirements. In the specific capacitance test, 30% H 2 SO 4 After the solution test, 10% H 3 PO 4 Solution test, the measured results are listed in Table 2.
[0059] Comparative Example 3
[0060] Take 40.0kg of tantalum oxide, the particle size of which is 2.04μm and the bulk density is 2.0g / cm 3, the numerical ratio is 2.04÷2.0=1.02, and the purity is 99.999%. Add 19.5kg of magnesium metal particles, and add 6.5kg of potassium chloride (KCl) and 6.5kg of sodium chloride (NaCl) at the same time, mix well and put into the reaction container, and separate the air in the reaction container. Pass argon gas into the reaction container, and put the reaction container into the heating furnace under the condition of maintaining positive pressure, heat it to 940℃, keep it warm for 2.0 hours, then reduce the temperature to 650℃ to evacuate, reduce the pressure in the reaction container to 5.7Pa, keep it warm for 18 hours, and stop evacuating. Then, pass argon gas into the reaction container and cool it down to room temperature, and passivate it. After the passivation is completed, it will be taken out of the furnace. When it is taken out of the furnace, the magnesium metal will catch fire and smoke; the obtained halide and tantalum powder mixture will be washed, pickled, filtered, and dried to separate the tantalum powder. The values of tantalum oxide Fee particle size, bulk density, purity, reduction temperature, etc. are listed in Table 1.
[0061] Then, 50 ppm of P was added to the tantalum powder and heated to 1400°C and below 5.0×10 -3 Pa pressure, high temperature and high vacuum heat treatment for 1.0 hour, and then deoxidation and acid washing to obtain the final tantalum powder. According to the anode block mass, pressing density, anode block sintering temperature, sintering time specified in Table 1, and other conditions according to the aforementioned GB / T3137 requirements, the final tantalum powder obtained is made into an anode block, energized under 200V conditions, and then the electrical properties are tested according to the aforementioned GB / T3137 requirements. In the specific capacitance test, 30% H 2 SO 4 After the solution test, 10% H 3 PO 4 Solution test, the measured results are listed in Table 2.
[0062] Example 4
[0063] Take 40.0kg of tantalum oxide, the particle size of which is 5.43μm and the bulk density is 1.8g / cm 3, the numerical ratio is 5.43÷1.8=3.02, and the purity is 99.9993%. Add 15.5kg of magnesium metal particles, and add 8.0kg of potassium chloride (KCl) and 8.0kg of sodium chloride (NaCl) at the same time, mix them evenly and put them into the reaction container, and separate the air in the reaction container. Pass a mixed gas of hydrogen and argon into the reaction container, control the hydrogen partial pressure to 50KPa, and keep the reaction container under positive pressure. Put the reaction container into a heating furnace and heat it, raise the temperature to 920℃, keep it warm for 2.0 hours, then reduce the temperature to 640℃ to evacuate, reduce the pressure in the reaction container to 5.7Pa, keep it warm for 18 hours, and stop evacuating. Then, pass argon into the reaction container and cool it down, cool it down to room temperature, and passivate it. After the passivation is completed, take it out of the furnace. When it is taken out of the furnace, the magnesium metal is stable and there is no ignition or smoke. The obtained mixture of halide and tantalum powder is washed with water, acid washed, filtered and dried to separate tantalum powder. The values of tantalum oxide particle size, bulk density, purity, reduction temperature, etc. are listed in Table 1.
[0064] Then, 50 ppm of P was added to the tantalum powder and heated at 1320°C and below 5.0×10 -3 Pa pressure, high temperature and high vacuum heat treatment for 1.0 hour, and then deoxidation and acid washing to obtain the final tantalum powder. According to the anode block mass, pressing density, anode block sintering temperature, sintering time specified in Table 1, and other conditions according to the aforementioned GB / T3137 requirements, the final tantalum powder obtained is made into an anode block, energized under 100V conditions, and then the electrical properties are tested according to the aforementioned GB / T3137 requirements. In the specific capacitance test, 30% H 2 SO 4 After the solution test, 10% H 3 PO 4 Solution test, the measured results are listed in Table 2.
[0065] Comparative Example 4
[0066] Take 40.0kg of tantalum oxide, the particle size of which is 1.66μm and the bulk density is 1.83g / cm 3, the numerical ratio is 1.66÷1.83=0.91, and the purity is 99.9993%. Add 18.5kg of magnesium metal particles, and add 8.0kg of potassium chloride (KCl) and 8.0kg of sodium chloride (NaCl) at the same time, mix well and put into the reaction container, and separate the air in the reaction container. Pass argon gas into the reaction container, and keep the reaction container in the positive pressure condition, put the reaction container into the heating furnace and heat it, raise the temperature to 920℃, keep it warm for 2.0 hours, then reduce the temperature to 640℃ to evacuate, reduce the pressure in the reaction container to 5.7Pa, keep it warm for 18 hours, and stop evacuating. Then, pass argon gas into the reaction container and cool it down to room temperature, and passivate it. After the passivation is completed, take it out of the furnace. When it is taken out of the furnace, the magnesium metal will catch fire and smoke. The obtained halide and tantalum powder mixture is washed with water, pickled, filtered, and dried to separate the tantalum powder. The values of tantalum oxide Fee particle size, bulk density, purity, reduction temperature, etc. are listed in Table 1.
[0067] Then, 50 ppm of P was added to the tantalum powder and heated at 1320°C and below 5.0×10 -3 Pa pressure, high temperature and high vacuum heat treatment for 1.0 hour, and then deoxidation and acid washing to obtain the final tantalum powder. According to the anode block mass, pressing density, anode block sintering temperature, sintering time specified in Table 1, and other conditions according to the aforementioned GB / T3137 requirements, the final tantalum powder obtained is made into an anode block, energized under 100V conditions, and then the electrical properties are tested according to the aforementioned GB / T3137 requirements. In the specific capacitance test, 30% H 2 SO 4 After the solution test, 10% H 3 PO 4 Solution test, the measured results are listed in Table 2.
[0068] Example 5
[0069] Take 40.0kg of tantalum oxide, the particle size of which is 3.86μm and the bulk density is 1.4g / cm 3, the tested ratio is 3.86÷1.4=2.75, and the purity is 99.9993%. 14.5kg of magnesium particles are added, and 9.0kg of potassium chloride (KCl) and 9.0kg of sodium chloride (NaCl) are added at the same time, mixed evenly, and then loaded into the reaction container, and the air in the reaction container is separated. A mixed gas of hydrogen and argon is introduced into the reaction vessel, and the hydrogen partial pressure is controlled to be 20KPa. The reaction vessel is placed in a heating furnace and heated under positive pressure, and the temperature is raised to 900°C, and the temperature is kept for 2.0 hours, and then the temperature is reduced to 640°C for evacuation, and the pressure in the reaction vessel is reduced to 5.7Pa, and the temperature is kept for 18 hours, and the evacuation is stopped. Then, argon is introduced into the reaction vessel again and the temperature is reduced to room temperature for passivation treatment. After the passivation is completed, the magnesium metal is taken out of the furnace, and there is no ignition and smoke phenomenon when it is taken out of the furnace; the obtained halide and tantalum powder mixture is washed with water, acid washed, filtered, and dried to separate the tantalum powder. The values of the tantalum oxide Fehler particle size, bulk density, purity, reduction temperature, etc. are listed in Table 1.
[0070] Then, 50 ppm of P was added to the tantalum powder and heated at 1280 °C and below 5.0 × 10 -3 Pa pressure, high temperature and high vacuum heat treatment for 1.0 hour, and then deoxidation and acid washing to obtain the final tantalum powder. According to the anode block mass, pressing density, anode block sintering temperature, sintering time specified in Table 1, and other conditions according to the aforementioned GB / T3137 requirements, the final tantalum powder obtained is made into an anode block, energized under 80V conditions, and then the electrical properties are tested according to the aforementioned GB / T3137 requirements. In the specific capacitance test, 30% H 2 SO 4 After the solution test, 10% H 3 PO 4 Solution test, the measured results are listed in Table 2.
[0071] Example 6
[0072] Take 40.0kg of tantalum oxide, the particle size of which is 3.86μm and the bulk density is 1.4g / cm 3, the numerical ratio is 3.86÷1.4=2.75, and the purity is 99.9993%. 13.0kg of magnesium particles are added, and 9.0kg of potassium chloride (KCl) and 9.0kg of sodium chloride (NaCl) are added at the same time, mixed evenly, and then loaded into the reaction container, and the air in the reaction container is separated. A mixed gas of hydrogen and argon is introduced into the reaction vessel, and the hydrogen partial pressure is controlled to be 20KPa. The reaction vessel is placed in a heating furnace and heated under positive pressure, and the temperature is raised to 900°C, and the temperature is kept for 2.0 hours, and then the temperature is reduced to 640°C for evacuation, and the pressure in the reaction vessel is reduced to 5.7Pa, and the temperature is kept for 18 hours, and the evacuation is stopped. Then, argon is introduced into the reaction vessel again and the temperature is reduced to room temperature for passivation treatment. After the passivation is completed, the magnesium metal is taken out of the furnace, and there is no ignition and smoke phenomenon when it is taken out of the furnace; the obtained halide and tantalum powder mixture is washed with water, acid washed, filtered, and dried to separate the tantalum powder. The values of the tantalum oxide Fehler particle size, bulk density, purity, reduction temperature, etc. are listed in Table 1.
[0073] Then, 50 ppm of P was added to the tantalum powder and heated at 1280 °C and below 5.0 × 10 -3 Pa pressure, high temperature and high vacuum heat treatment for 1.0 hour, and then deoxidation and acid washing to obtain the final tantalum powder. According to the anode block mass, pressing density, anode block sintering temperature, sintering time specified in Table 1, and other conditions according to the aforementioned GB / T3137 requirements, the final tantalum powder obtained is made into an anode block, energized under 80V conditions, and then the electrical properties are tested according to the aforementioned GB / T3137 requirements. In the specific capacitance test, 30% H 2 SO 4 After the solution test, 10% H 3 PO 4 Solution test, the measured results are listed in Table 2.
[0074] Example 7
[0075] Take 40.0kg of tantalum oxide, the particle size of which is 2.62μm and the bulk density is 0.79g / cm 3, the numerical ratio is 2.62÷0.79=3.32, and the purity is 99.9993%. 14.5kg of magnesium particles are added, and 9.0kg of potassium chloride (KCl) and 9.0kg of sodium chloride (NaCl) are added at the same time, mixed evenly, and then loaded into the reaction container, and the air in the reaction container is separated. A mixed gas of hydrogen and argon is introduced into the reaction container, and the hydrogen partial pressure is controlled to be 20KPa. The reaction container is placed in a heating furnace and heated under positive pressure, and the temperature is raised to 860°C, and the temperature is kept for 2.0 hours, and then the temperature is reduced to 640°C for evacuation, and the pressure in the reaction container is reduced to 5.7Pa, and the temperature is kept for 18 hours, and the evacuation is stopped. Then, argon is introduced into the reaction container and the temperature is reduced to room temperature for passivation treatment. After the passivation is completed, the magnesium metal is taken out of the furnace, and there is no ignition and smoke phenomenon when it is taken out of the furnace; the obtained halide and tantalum powder mixture is washed with water, acid washed, filtered, and dried to separate the tantalum powder. The values of the tantalum oxide Fehler particle size, bulk density, purity, reduction temperature, etc. are listed in Table 1.
[0076] Then, 70 ppm of P was added to the tantalum powder and heated to 1230 °C and below 5.0 × 10 -3 Pa pressure, high temperature and high vacuum heat treatment for 1.0 hour, and then deoxidation and pickling are carried out to obtain the final tantalum powder. According to the anode block mass, pressing density, anode block sintering temperature, sintering time specified in Table 1, and other conditions according to the aforementioned GB / T3137 requirements, the final tantalum powder obtained is made into an anode block, energized under 60V conditions, and then the electrical properties are tested according to the aforementioned GB / T3137 requirements. In the specific capacitance test, 30% H 2 SO 4 After the solution test, 10% H 3 PO 4 Solution test, the measured results are listed in Table 2.
[0077] Example 8
[0078] Take 40.0kg of tantalum oxide, the particle size of which is 2.62μm and the bulk density is 0.79g / cm 3, the numerical ratio is 2.62÷0.79=3.32, and the purity is 99.9993%. 12.0 kg of magnesium particles are added, and 9.0 kg of potassium chloride (KCl) and 9.0 kg of sodium chloride (NaCl) are added at the same time, mixed evenly, and then loaded into the reaction container, and the air in the reaction container is separated. A mixed gas of hydrogen and argon is introduced into the reaction container, and the hydrogen partial pressure is controlled to be 20KPa. The reaction container is placed in a heating furnace and heated under positive pressure, and the temperature is raised to 860°C, and the temperature is kept for 2.0 hours, and then the temperature is reduced to 640°C for evacuation, and the pressure in the reaction container is reduced to 5.7Pa, and the temperature is kept for 18 hours, and the evacuation is stopped. Then, argon is introduced into the reaction container and the temperature is reduced to room temperature for passivation treatment. After the passivation is completed, the magnesium metal is taken out of the furnace, and there is no ignition and smoke phenomenon when it is taken out of the furnace; the obtained halide and tantalum powder mixture is washed with water, acid washed, filtered, and dried to separate the tantalum powder. The values of the tantalum oxide Fehler particle size, bulk density, purity, reduction temperature, etc. are listed in Table 1.
[0079] Then, 70 ppm of P was added to the tantalum powder and heated to 1230 °C and below 5.0 × 10 -3 Pa pressure, high temperature and high vacuum heat treatment for 1.0 hour, and then deoxidation and pickling are carried out to obtain the final tantalum powder. According to the anode block mass, pressing density, anode block sintering temperature, sintering time specified in Table 1, and other conditions according to the aforementioned GB / T3137 requirements, the final tantalum powder obtained is made into an anode block, energized under 60V conditions, and then the electrical properties are tested according to the aforementioned GB / T3137 requirements. In the specific capacitance test, 30% H 2 SO 4 After the solution test, 10% H 3 PO 4 Solution test, the measured results are listed in Table 2.
[0080] Example 9
[0081] Take 40.0kg of tantalum oxide, the particle size of which is 2.62μm and the bulk density is 0.79g / cm 3, the numerical ratio is 2.62÷0.79=3.32, and the purity is 99.9993%. 14.5kg of magnesium particles are added, and 9.0kg of potassium chloride (KCl) and 9.0kg of sodium chloride (NaCl) are added at the same time. After mixing evenly, they are loaded into a reaction container, and a crucible is put in which 1.0kg of tantalum powder containing 3500ppm of hydrogen is put, and the air in the reaction container is separated. Argon gas is introduced into the reaction vessel, and the reaction vessel is placed in a heating furnace under positive pressure. The temperature is raised to 860°C, and the temperature is kept for 2.0 hours. Then the temperature is reduced to 640°C for evacuation. The pressure in the reaction vessel is reduced to 5.7 Pa, and the temperature is kept for 18 hours. The evacuation is stopped, and then argon gas is introduced into the reaction vessel again and the temperature is reduced to room temperature for passivation treatment. After the passivation is completed, the magnesium metal is taken out of the furnace. When taken out of the furnace, it is stable without ignition and smoke. The obtained halide and tantalum powder mixture is washed with water, acid washed, filtered, and dried to separate the tantalum powder. The values of the tantalum oxide Fehler particle size, bulk density, purity, reduction temperature, etc. are listed in Table 1.
[0082] Then, 70 ppm of P was added to the tantalum powder and heated to 1230 °C and below 5.0 × 10 -3 Pa pressure, high temperature and high vacuum heat treatment for 1.0 hour, and then deoxidation and pickling are carried out to obtain the final tantalum powder. According to the anode block mass, pressing density, anode block sintering temperature, sintering time specified in Table 1, and other conditions according to the aforementioned GB / T3137 requirements, the final tantalum powder obtained is made into an anode block, energized under 60V conditions, and then the electrical properties are tested according to the aforementioned GB / T3137 requirements. In the specific capacitance test, 30% H 2 SO 4 After the solution test, 10% H 3 PO 4 Solution test, the measured results are listed in Table 2.
[0083] Example 10
[0084] Take 40.0kg of tantalum oxide, the particle size of which is 1.27μm and the bulk density is 0.50g / cm 3, the numerical ratio is 1.27÷0.50=2.54, and the purity is 99.9993%. 14.5kg of magnesium particles are added, and 10.0kg of potassium chloride (KCl) and 10.0kg of sodium chloride (NaCl) are added at the same time, mixed evenly, and then loaded into the reaction container, and the air in the reaction container is separated. A mixed gas of hydrogen and argon is introduced into the reaction vessel, and the partial pressure of hydrogen is controlled to be 20KPa. The reaction vessel is placed in a heating furnace and heated under positive pressure, and the temperature is raised to 850°C, and the temperature is kept for 2.0 hours, and then the temperature is reduced to 640°C for evacuation, and the pressure in the reaction vessel is reduced to 5.7Pa, and the temperature is kept for 18 hours, and the evacuation is stopped. Then, argon is introduced into the reaction vessel and the temperature is reduced to room temperature for passivation treatment. After the passivation is completed, the magnesium metal is taken out of the furnace, and there is no ignition and smoke phenomenon when it is taken out of the furnace; the obtained halide and tantalum powder mixture is washed with water, acid washed, filtered, and dried to separate the tantalum powder. The values of the tantalum oxide Fehler particle size, bulk density, purity, reduction temperature, etc. are listed in Table 1.
[0085] Then, 70 ppm of P was added to the tantalum powder and heated at 1180 °C and below 5.0 × 10 -3 Pa pressure, high temperature and high vacuum heat treatment for 1.0 hour, and then deoxidation and pickling are carried out to obtain the final tantalum powder. According to the anode block mass, pressing density, anode block sintering temperature, sintering time specified in Table 1, and other conditions according to the aforementioned GB / T3137 requirements, the final tantalum powder obtained is made into an anode block, energized under 40V conditions, and then the electrical properties are tested according to the aforementioned GB / T3137 requirements. In the specific capacitance test, 30% H 2 SO 4 After the solution test, 10% H 3 PO 4 Solution test, the measured results are listed in Table 2.
[0086] Embodiment 11
[0087] Take 40.0kg of tantalum oxide, the particle size of which is 1.27μm and the bulk density is 0.50g / cm 3, the numerical ratio is 1.27÷0.50=2.54, and the purity is 99.9993%. 14.5kg of magnesium particles are added, and 10.0kg of potassium chloride (KCl) and 10.0kg of sodium chloride (NaCl) are added at the same time, mixed evenly and loaded into the reaction container; another crucible is put into which 1.0kg of tantalum powder containing 3500ppm of hydrogen is put, and the air in the reaction container is separated. Argon gas is introduced into the reaction vessel, and the reaction vessel is placed in a heating furnace under positive pressure. The temperature is raised to 850°C, and the temperature is kept for 2.0 hours. Then the temperature is reduced to 640°C for evacuation. The pressure in the reaction vessel is reduced to 5.7 Pa, and the temperature is kept for 18 hours. The evacuation is stopped, and then argon gas is introduced into the reaction vessel again and the temperature is reduced to room temperature for passivation treatment. After the passivation is completed, the magnesium metal is taken out of the furnace. When taken out of the furnace, it is stable without ignition and smoke. The obtained halide and tantalum powder mixture is washed with water, acid washed, filtered, and dried to separate the tantalum powder. The values of the tantalum oxide Fehler particle size, bulk density, purity, reduction temperature, etc. are listed in Table 1.
[0088] Then, 70 ppm of P was added to the tantalum powder and heated at 1180 °C and below 5.0 × 10 -3 Pa pressure, high temperature and high vacuum heat treatment for 1.0 hour, and then deoxidation and pickling are carried out to obtain the final tantalum powder. According to the anode block mass, pressing density, anode block sintering temperature, sintering time specified in Table 1, and other conditions according to the aforementioned GB / T3137 requirements, the final tantalum powder obtained is made into an anode block, energized under 40V conditions, and then the electrical properties are tested according to the aforementioned GB / T3137 requirements. In the specific capacitance test, 30% H 2 SO 4 After the solution test, 10% H 3 PO 4 Solution test, the measured results are listed in Table 2.
[0089] Table 1 Main process parameters
[0090]
[0091] Table 2 Electrical properties of finished tantalum powder
[0092]
[0093]
[0094] From Table 2 we can see that:
[0095] The present invention is suitable for manufacturing tantalum powder for high-voltage and high-reliability capacitors with higher specific capacitance. Compared with the comparative example, the energizing block obtained in the embodiment has a high specific capacitance under relatively high voltage conditions, and the breakdown voltage test shows that it has a high breakdown voltage.
[0096] It can also be seen from Table 1 that after energization, the anode block made of the tantalum powder of the present invention was heated to room temperature using different acid solutions (using 30% H 2 SO 4 The solution was mixed with 10% HO 3 PO 4 The difference in specific capacitance of the embodiment obtained by the test of the tantalum powder (solution) is smaller than that of the prior art (i.e., the corresponding comparative example). It is generally believed that phosphoric acid and sulfuric acid have different surface tensions and different abilities to penetrate into the ultrafine pores in the anode block. Therefore, the difference in specific capacitance reflects the amount of ultrafine pores in the anode block. Therefore, the results in the table prove that the anode block with fewer ultrafine pores can be obtained by using the tantalum powder according to the present invention.
Claims
1. A method for preparing tantalum powder by reducing tantalum oxide powder raw material with alkaline earth metal such as magnesium (preferably magnesium particles), characterized in that The tantalum oxide powder raw materials used are the Fisher particle size (in μm) and the bulk density (in g / cm 3 Tantalum oxide powder having a ratio of Fischer-Tropsch particle size to bulk density greater than 1.5, and an atmosphere containing hydrogen-containing gas is used during the reduction process. Preferably, the ratio of the Fischer-Tropsch particle size to the bulk density of the high-purity tantalum oxide powder is preferably greater than 2.0, preferably greater than 3.0, more preferably greater than 3.5, more preferably greater than 4.5; for example, 2.0-15.0, more preferably 3.0-5.
0.
2. The method according to claim 1, wherein the tantalum oxide powder raw material is high-purity tantalum oxide of 99.995% or more, more preferably 99.999% or more.
3. A method for preparing tantalum powder by reducing tantalum oxide with an alkaline earth metal such as magnesium (preferably magnesium particles), comprising the following steps: (1) Select the particle size (in μm) and the bulk density (in g / cm 3 The tantalum oxide powder with a ratio of greater than 1.5 to tantalum oxide is used as a raw material, the tantalum oxide powder is mixed with an excess of an alkaline earth metal reducing agent, and at the same time, 10-200% by weight of at least one alkali metal and / or alkaline earth metal halide is mixed, and the mixture is placed in a sealed reaction container, the air in the container is evacuated, and the container is placed in a heating furnace; (2) raising the temperature of the heating furnace to 700-1000° C. and maintaining the temperature for, for example, 1-3 hours, to allow the tantalum oxide to fully react with the reducing agent; (3) After the insulation is completed, the temperature of the heating furnace is set at 600-750° C., the heating furnace is evacuated, for example, to below 10 Pa, and the temperature is maintained under negative pressure (for example, for 1-10 hours); (4) Then, an inert gas is filled into the reaction container to maintain a positive pressure in the reaction container, and then the reaction container is cooled to room temperature and passivated to obtain a mixture containing a halide and tantalum powder; (5) separating tantalum powder from the obtained mixture, for example, by washing with water, washing with acid, filtering, or drying. Wherein, in step (1), after the air in the container is evacuated, the atmosphere in the container is made to contain a hydrogen-containing gas, for example, by introducing a hydrogen-containing gas (for example, pure hydrogen, or a mixture of hydrogen and an inert gas), or by adding a hydrogen-containing substance (for example, metallic tantalum adsorbed with hydrogen) and causing it to release hydrogen.
4. The manufacturing method according to claim 3, characterized in that: The amount of reducing agent added in step (1) is 5-50% of the theoretical amount for complete reduction of tantalum oxide, preferably 10-48%, more preferably 10-45%, even more preferably 10-15%, 5-10%, or 15-20%.
5. The manufacturing method according to claim 3 or 4, characterized in that: The weight of the alkali metal chloride added in step (1) is 10-180% of the weight of tantalum oxide, preferably 25-120%, more preferably 70-120% or 100-180%, most preferably 15-80%, for example 25-80%.
6. The manufacturing method according to any one of claims 3 to 5, characterized in that: The alkali metal or alkaline earth metal halide in step (1) is a mixture of one or more of NaCl, KCl, KF, KI, MgCl2, preferably a mixture of NaCl and KCl, more preferably a mass ratio of sodium chloride to potassium chloride in the mixture is 1:1-10, most preferably about 1:
1.
7. The manufacturing method according to any one of claims 3 to 6, characterized in that: In step (1), one or more compounds containing B, P, and / or N elements are added as additives to dope the tantalum powder. Preferably, the amount of B element added is 1-100 ppm, more preferably 20-60 ppm, based on the amount of effective elements. and / or the added P element is 10-200ppm, more preferably 30-90ppm; And / or the added N element is 300-2500ppm, more preferably 500-1200ppm.
8. The manufacturing method according to any one of claims 3 to 7, characterized in that: The hydrogen partial pressure in step (2) exceeds 0.050 KPa, preferably 0.1-200 KPa, more preferably 0.3-50 KPa, more preferably 0.3-20 KPa, even more preferably 0.5-2 KPa or 2-8 KPa, even more preferably 0.1-0.3 KPa.
9. The manufacturing method according to any one of claims 3 to 8, further comprising after step 5): High temperature and high vacuum heat treatment; Reduce oxygen, for example by adding a small amount of magnesium particles; and The separation is carried out, for example, by acid washing, filtering, and drying.
10. Tantalum powder produced by the production method according to any one of claims 2 to 9, and an anode block made of the tantalum powder, and use thereof in producing a capacitor.
Citation Information
Patent Citations
Method for preparing low chemical valence niobium oxide or niobium powder
CN101139110A
Preparation method of tantalum powder for capacitor
CN101574741A
Method for producing tantalum powder for capacitor by reducing tantalum oxide with alkaline earth metal
CN114192791A
Preparation method of tantalum powder with high purity and large apparent density and tantalum powder prepared by method
CN118371718A
Tantalum powder, method for producing same powder and sintered anodes obtained from it
CN1247576A